Hubungan Peran Orang Tua Dengan Kemandirian Personal Hygiene Pada Anak Pra Sekolah Di RA Nurulhasanah Percut Sei Tuan - Nodalima Gulo; Muhammad Taufik Daniel Hasibuan; Dior Manta Tambunan (Universitas Murni Teguh, 2025)
Personal hygiene or personal hygiene is an effort to maintain personal cleanliness and health, both physically and mentally. Pre-school children are still in the developmental stage and need parental guidance in forming independent hygiene habits. Important in teaching and familiarizing children with personal hygiene from an early age. This study aims to determine the relationship between the role of parents and the personal hygiene of pre-school children in Ra Nurul Hasanah Percut Sei Tuan. This research used quantitative methods with a cross-sectional approach. The number of samples in this study was 92 people with total sampling techniques. Data was collected using a questionnaire and analyzed using the Spearman’s Rho statistical. The results of the bivariate analysis showed that there is a significant relationship between the role of parents and the independence of personal hygiene in pre-school children with a p-value = 0,000 (α <0.05), this shows that the better the role of parents, the higher the level of independence of children in maintaining personal hygiene. It is concluded that there is a significant relationship between the role of parents and personal hygiene independence in preschool children. Therefore, parent active role in providing education and guidance regarding personal hygiene is very necessary to from healthy living habits in children from an early age. It is recommended for further research to do experimental study in measuring the effectiveness of parents in forming personal hygiene habits in children.